Control de inventario en la importadora jorua cía ltda del cantón Babahoyo, año 2021 - Cabrera Aguilera, Keila Lilibeth (2022)
The following case study addressed the issue of inventory control in Importadora Jorua, which is dedicated to the sale of medical supplies in the city of Babahoyo. Our study is focused on its problem, which is the inefficient inventory control system, its main objective is to analyze it and be able to draw a conclusion with an efficient recommendation, for which we know that inventories are very important in companies. We know that every company must have a good inventory control system, because through them you can reduce losses and control the products that exist in said entity. Good inventory control helps and above all ensures that the inventory is available when required. For the development of this present case study, an analytical investigation and a solid search of bibliographical references were carried out.